Path Analysis on the Associations between Infertility, Stress, and Depression among Women in Surakarta, Central Java - Retiyansa, Yesi; Indarto, Dono; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: In patriarchal societies like Indonesia, infertility is culturally considered as a problem of women. Most of the burden of infertility is borne by women because of a rapid decline in fertility with age, societal pressure and stigma. Infertility can affect psychological disorders such as stress and depression. This study aimed to examine the associations between infertility, stress, and depression among women in Surakarta, Central Java. Subjects and Method: This was